MACROSCOPIC, MORPHOLOGIC AND MORPHOMETRIC ASPECTS OF THE SPLEEN OF RATS AFTER TOTAL CLAMPING OF THE HEPATIC PEDICLE ASPECTOS MACROSCÓPICOS, MORFOLÓGICOS E MORFOMÉTRICOS DO BAÇO DE RATOS APÓS O CLAMPEAMENTO TOTAL DO PEDÍCULO HEPÁTICO - Lázaro Manoel Camargo; Manuel Jesus Simões; Fabio Souza Mendonça; Renato Gebara Sampaio Dória; Joaquim Evêncio-Neto; Silvio Henrique Freitas; Abrão Antonio Sébe (Ciência Animal Brasileira, 2009)
One of the complications of hepatic pedicle total clamping is the splanchnic congestion and consequently a splenic congestion. The aim of this study was to observe the macro and microscopic alterations that occurred in the spleen during an ischemia produced by the hepatic pedicle clamping. Fourth male rats were divided in four groups of ten animals each. The control group (C) was not submitted to ischemia and the experimental groups (E1, E2 and E3) were submitted to the total clamping during 10, 20 and 30 minutes, respectively. After these periods, spleen fragments were collected and histological analyzed by the eosin-hematoxilin and ferric ferrocyanide staining technique. The results showed microscopic alterations at the E1, E2 and E3 groups that permitted to conclude that the total clamping of the hepatic pedicle promote intense vascular congestion, increase of the hemosiderin granules, decrease of the white pulp and increase of the red pulp, being these alterations more pronounced at the 30 minutes. KEY WORDS: Congestion, hemossiderina, spleen, rats. Uma das complicações do clampeamento total do pedículo hepático é a congestão esplâncnica e, consequentemente, a congestão esplênica. Este trabalho teve como objetivo observar as alterações macroscópicas, morfológicas e morfométricas que ocorreram no baço com a isquemia produzida pelo clampeamento do pedículo hepático. Para tanto, utilizaram-se quarenta ratos machos, divididos em quatro grupos de dez animais. Não se submeteu o grupo controle (C) à isquemia. Por sua vez, submeteram-se os grupos experimentais (E1, E2 e E3) ao clampeamento total por dez, vinte e trinta minutos, respectivamente. Após esses períodos, fragmentos do baço foram retirados e analisados histologicamente pela técnica de Hematoxilina-eosina e Ferrocianeto-férrico. Os resultados mostraram alterações microscópicas nos grupos E1, E2 e E3, que permitem concluir que o clampeamento total do pedículo hepático promove intensa congestão vascular, aumento de grânulos de hemossiderina, diminuição da polpa branca e aumento da polpa vermelha, sendo essas alterações mais intensas aos trinta minutos. PALAVRAS-CHAVES: Baço, congestão, hemossiderina, rato.